SEKSISME DALAM NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM KARYA DIAN PURNOMO: ANALISIS WACANA KRITIS SARA MILLS - Ningsih, Anisa Nurani; Ratnasari, Andaru (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to describe overt or direct sexism and indirect sexism in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo, using Sara Mills' critical discourse analysis approach. Sexism is understood as language that discriminates against women by depicting them negatively and considering activities related to women as trivial. By analyzing sexism, attention can be drawn to the way language is used to represent women, as well as discrimination against women. This research method is a descriptive qualitative method. The results of the study found five types of overt or direct sexism, namely terms of insult to women, semantic insults, transitivity, reported speech, jokes and six types of indirect sexism, namely humor, presupposition or estimation, conflicting messages, scripts and metaphors, collocations, and androcentric perspectives. The most dominant type is transitivity in the form of objectification of women and androcentric perspective in the form of patriarchy. This work is a critical reflection of social practices that still shackle women in society.